Review on the Risk Assessment of Heavy Metals in Malaysian Clams - Md. Faruk Hossen; Sinin Hamdan; Md. Rezaur Rahman (The Scientific World Journal)
The current review discusses the levels of six heavy metals in different clam species from 34 sites of Malaysian coasts. The concentrations (µg/g dry weight) of these heavy metals ranged around 0.18–8.51, 0.13–17.20, 2.17–7.80, 0.84–36.00, 24.13–368.00, and 177.82–1912.00 for Cd, Pb, Ni, Cu, Zn, and Fe, respectively. It was observed that the concentrations of metals slightly depend on different clam species but mostly depend on site locations. According to Malaysian Food Regulation (1985), about 30% and more than 50% sites are safe from Cd and Pb contamination, respectively, and also the clam species from the other populations studied were safe for consumption.